THE EFFECT OF QUICK RATIO, DEBT TO EQUITY RATIO, EARNING PER SHARE, PRICE TO BOOK VALUE AND RETURN ON EQUITY ON STOCK RETURN WITH MONEY SUPPLY AS MODERATED VARIABLES (Study of Banking Companies Listed on Indonesia Stock Exchange Period 2008 - 2017) - Martina, Sri (Asosiasi Dosen Akuntansi Indonesia, 2019)
The purpose of this study is to empirically analyse the Effect of Quick Ratio (QR), Debt To Equity Ratio (DER), Earning Per Share (EPS), Price To Book Value (PBV) and Return On Equity (ROE) on Stock Returns with Money Supply (MS) as a Moderation variable. The period of this study was from 2008 to 2017 and the sample population of the company were 23 banking companies listed on the Indonesia Stock Exchange. Data were analysed using multiple linear regression methods. And to test the moderating variables using the Residual test. The results found that QR, DER, EPS, PBV, and ROE significantly affect stock returns simultaneously, but partially only EPS and PBV variables have a positive and significant effect on stock returns. QR, DER has a negative and not significant effect on stock returns while ROE has no effect on stock returns. MS cannot moderate the relationship between QR, DER, EPS, PBV and ROE with stock returns on banking companies listed on the Indonesia Stock Exchange.